The Correlation between Cognitive Styles and Student’s Reading Comprehension - Putri Nurus Sakina; Desi Surlitasari Dewi; Aulia Putri (ANGLO-SAXON: Jurnal Ilmiah Program Studi Pendidikan Bahasa Inggris, 2017)
The objective of this study was to find out whether there is any correlation between cognitive style and student’s reading comprehension. The researcher limited the cognitive style in this study in Field Dependence and Field Independence. For example, students with Field dependence tend to have low reading comprehension because they difficult to construct their own perception and to find the information that not exactly written in the text.  The research design was correlational research. The population of this research was 271 students of Eleventh Grade of SMAN 3 Batam in the Academic Year 2015/2016. The population was selected simple random sampling technique. Embedded Figure Test (EFT) and Reading comprehension test were used as the instrument of this research. Then the researcher analyzed the correlation by using Spearman Ranked Correlation formula to correlate both cognitive style (variable X) and students reading comprehension (variable Y). The result showed that Zcountedis 5.157 and Ztableis 1.96. It means Zcountedis greater than Ztableand Ho is rejected and Ha is accepted. The researcher found out that there was a significant correlation between cognitive style and student’s Reading Comprehension at Eleventh Grade of SMAN 3 Batam in the Academic Year 2015/2016.Keywords : cognitive style, field dependence, field independence and reading comprehension.